2022
DOI: 10.1590/fst.96821
|View full text |Cite
|
Sign up to set email alerts
|

Extracts with anti-inflammatory activities from Acanthopanax trifoliatus (L.) Merr. by inhibiting LPS-induced expression of iNOS and COX-2

Abstract: Acanthopanax trifoliatus (L.) Merr. have been used as folk medicine to treat various diseases traditionally and the young leaves and shoots of A. trifoliatus are popularly consumed as vegetables and herbal tea in southern China. In the study, we firstly tested the cytotoxicity and NO production of 18 fractions that extracted from the leaves, stems and roots of A. trifoliatus to select the bioactive fraction. The increasing evidence suggested that the dichloromethane extract prepared from stems of A. trifoliatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In contemporary times, natural compounds, especially those found in foods, have gained enormous attention in medicine due to their immense bioactivity. These bioactivities include antioxidant and anti-inflammatory properties ( Cheng et al, 2010 ; Luo et al, 2022 ). The anti-inflammatory effects of RES and vitamin E have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In contemporary times, natural compounds, especially those found in foods, have gained enormous attention in medicine due to their immense bioactivity. These bioactivities include antioxidant and anti-inflammatory properties ( Cheng et al, 2010 ; Luo et al, 2022 ). The anti-inflammatory effects of RES and vitamin E have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, natural compounds especially in foods have been arresting considerable attention in the field of pharmaceuticals and cosmetics due to their extensive bioactivities such as anti-oxidant and anti-inflammatory effects (Luo et al, 2022b). RES or VE have been shown to have anti-inflammatory effects as different natural products.…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al (2018) investigated that Acanthopanacis cortexgold nanoparticles (A-AuNPs) suppressed NF-κB and AP-1 through phosphorylation of MAPKs signaling in RAW264.7 cells and inhibited the LPS-induced production of iNOS and COX-2 (Ahn et al, 2018). Luo et al (2021b) reported that the anti-inflammatory activities of dichloromethane extract from A. trifoliatus stems by inhibiting LPS-induced expression of iNOS and COX-2 (Luo et al, 2021b). Eun et al (2021) investigated the Antiosteoporosis effects of Eleutherococcus senticosus, Achyranthes japonica, and Atractylodes japonica mixed extract fermented with nuruk and suggested that it could be a potential therapeutic candidate for the treatment of osteoclast-mediated inflammatory bone diseases (Eun et al, 2021).…”
Section: Effect Of Alsdc On Inos and Cox-2 Protein Expressionmentioning
confidence: 99%
“…This research provides evidence of the possible beneficial health advantages of A. leucorrhizus and furnished a reliable theoretical and practical basis for the developing and utilizing Acanthopanax species. symptoms of the inflammation, such as A. senticosus (Fei et al, 2014;Fan et al, 2019;Jin et al, 2020), A. gracilistylus (Liu et al, 2017;Zou et al, 2017;Xu et al, 2018;Luo et al, 2021a), and A. trifoliatus (Wang et al, 2015;Chien et al, 2015;Luo et al, 2021b), the mechanism of A. leucorrhizus stems on its antiinflammation activity is still not well known. For the purpose of developing and utilizing Acanthopanax species, we focused our study on the anti-inflammatory properties of various fractions of A. leucorrhizus stems through the effects on the production of NO, TNF-α, and IL-6, as well as on the expression of iNOS and COX-2 by LPS-induced RAW 264.7 macrophages.…”
Section: Introductionmentioning
confidence: 99%